Kebijakan Pelayanan Kesehatan di Desa Rato’ombu, Kecamatan Lage, Kabupaten Poso - Mohammad Rusli Syuaib (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study aims to analyze the village government policy in providing health services for the community in Rato'ombu Village, Lage District, Poso Regency, and identify the factors that influence it. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation of eight informants. The results of the study indicate that the coverage of health services provided has reached most of the community, although it is still necessary to increase the capacity of human resources, especially health workers. Internal factors that influence the policy include communication, complaint facilities, and the availability of health workers. External factors include inconsistencies in registration data, incomplete treatment requirements, and obstacles to paying BPJS contributions. This study is important because it provides input for the village government in formulating more effective and inclusive health service policies. The main contribution of this study lies in policy recommendations that can strengthen the village health service system, in line with the direction of national policy in strengthening basic services at the local level.